OM85 ameliorates bleomycin-induced pulmonary fibrosis in mice by inhibiting Notch expression and modulating the IFN-γ/IL-4 ratio - Yaling Yu; Zhuanyun Li; Zhenghao Hu; Tianfeng Peng; Ruijie Niu; Peng Sun; Xiaorong Wang; Jinnong Zhang (Scientific Reports, 2025)
Abstract Th1/Th2 balances may play a vital role in the processes of inflammation and fibrosis. The Th1/Th2 paradigm can be evaluated by representing IFN-γ for Th1 and IL-4 for Th2. OM-85 BV encouraged preferential development of the Th1-type immunity characterized by amplified IFN-γ and decreased IL-4 production. This study aimed to evaluate the inhibitory effect of OM85 on bleomycin (BLM)-induced pulmonary fibrosis in C57 and its possible mechanisms. In vitro experiments demonstrated that OM85 exhibited no significant toxicity to HELF cells. OM-85 inhibited the TGF-β1-induced protein expression of Notch1 and Hes1 and reduced the fibrosis-related marker profiles, such as collagen I, collagen III, fibronectin, P21, and α-SMA, following TGF-β1 treatment of these cells. Immunofluorescence also revealed that OM-85 decreased the expression of α-SMA induced by TGF-β1 in HELF cells. In the vivo experiments, a pulmonary fibrosis model was established by administering three intratracheal doses of BLM (1 mg/kg). The BLM-OM85 group was exposed to an aerosol containing 10.5 mg of OM-85 dissolved in 10 mL of sterile PBS on days 42, 44, 46, 49, 51, and 53. BLM-induced pulmonary fibrosis, leading to increased levels of lung hydroxyproline, total cell count, macrophages, neutrophils, lymphocytes, and the expression of TGF-β1 as well as Notch1 and Hes1 in lung tissue, along with fibrosis-associated proteins such as collagen I, collagen III, fibronectin, P21, and α-SMA. Additionally, the Th1 response was suppressed, as evidenced by decreased IFN-γ in the bronchoalveolar lavage fluid (BALF), while the Th2 response was amplified, marked by increased IL-4 levels in BALF. Moreover, morphological assessments showed that BLM caused increased Ashcroft scores, relative collagen content, and an expanded damaged area, as well as an increased optical density (OD) of collagen I. The administration of OM-85 significantly mitigated these effects. These findings suggest that OM-85 holds therapeutic potential for BLM-induced pulmonary fibrosis in female C57 mice, partly due to the inhibition of Notch1 and Hes1 expression and the modulation of the IFN-γ/IL-4 ratio.